Utilization of Canva-Based Information Technology in Interactive Learning Media to Improve Learning Effectiveness in Vocational High Schools (SMK) - Sitorus, Hammuda; Giatman, Muhammad; Effendi, Hansi; Dony, Phil (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the use of Canva-based information technology as an interactive learning medium to improve learning effectiveness in Vocational High Schools (SMK). The use of Canva allows teachers to design materials that are more visual, engaging, and easily understood by students. Interactive designs produced through this platform are believed to increase learning motivation, active student engagement, and strengthen conceptual understanding in various vocational subjects. This study uses a descriptive approach by reviewing the implementation of Canva in the learning process, including planning, implementation, and student responses to the media used. The results show that Canva makes a positive contribution to learning effectiveness by increasing learning interest, ease of access to materials, and flexibility in content presentation. Thus, the use of Canva is recommended as an alternative, innovative learning medium in vocational high schools to support a more effective and engaging educational process.